Pemanfaatan Photosynthetic Bacteria sebagai Biofertilizer di Desa Bakalan - Anggi Indah Yuliana; Mochammad Syafiuddin Shobirin; Azhar Irfana Gangsar; Dwi Indah Lestari; Safitri Safitri (LPPM Universitas KH. A. Wahab Hasbullah, 2026)
This study aims to enhance farmers’ understanding and skills in utilizing organic fertilizer based on Photosynthetic Bacteria (PSB) in Bakalan Village, Sumobito District, Jombang Regency. This community service program was implemented through outreach and training activities, focusing on the introduction and practice of PSB fertilizer production as an alternative to the currently dominant chemical fertilizers. The methods applied included face-to-face approaches, participatory discussions, and direct demonstrations of PSB production techniques using locally available materials. The results indicated a positive response from the participants. Most of them showed improved knowledge about the benefits of PSB fertilizer and developed practical skills in its production process. In addition, they gained a better understanding of the importance of using environmentally friendly organic fertilizers to support sustainable agriculture. Evaluation findings revealed a high level of acceptance toward this innovation. Nevertheless, challenges remain, particularly the farmers’ tendency to prefer chemical fertilizers due to their practicality and the limited availability of raw materials in larger quantities. Overall, this activity demonstrates great potential in promoting sustainable agriculture while raising public awareness of the importance of innovations based on local wisdom. The utilization of PSB as an organic fertilizer is expected not only to support increased agricultural productivity but also to improve environmental quality and reduce dependence on chemical fertilizers.